Preparation method of alumina-based conductive ceramic based on CuAlO2 phase

By introducing the CUALO2 phase in alumina ceramics, the problem of complex and high energy consumption of existing alumina ceramics thermal heating system was solved, and low -temperature sintering and conductive transformation were realized, reducing costs and energy consumption, preparing excellent performance Conductive heating ceramics.

CN119330689APending Publication Date: 2025-01-21NORTHEASTERN UNIV AT QINHUANGDAO

Patent Information

Application Number
CN202411459165.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The preparation process of existing alumina ceramic heating bodies is complex, requiring high temperature co-fired metal and alumina, resulting in high energy consumption and increased costs.

Method used

By introducing CUALO2 as a conductive in alumina ceramics, it is continuously distributed along the aluminum oxide crystal boundary to form conductive channels, thereby realizing low -temperature sintering and conductive transformation.

Benefits of technology

The sintering temperature of alumina ceramics is reduced from 1600°C to 1000-1500°C, complex atmosphere sintering is avoided, the operation is simple, the raw material cost and preparation energy consumption are low, and conductive heating ceramics with excellent performance are prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330689A_ABST
    Figure CN119330689A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a CuAlO2-phase-based alumina-based conductive ceramic, and belongs to the technical field of preparation of nano conductive ceramics. The invention relates to a method for converting aluminum oxide ceramic into a novel electric heating element from an insulator by adding a semiconductor component CuAlO2 phase in the aluminum oxide ceramic and continuously distributing the CuAlO2 phase along an aluminum oxide crystal boundary through a process to form a conductive path, which comprises the following steps of: mixing CuO, SiO2, Al2O3 and the like according to a certain proportion, and carrying out ball milling; and the novel aluminum oxide electric heating body is formed after tabletting and sintering. According to the method, the sintering temperature of the aluminum oxide ceramic can be greatly reduced, and complicated processes and equipment are not needed, so that the novel aluminum oxide conductive heating ceramic is low in energy consumption, simple in process, low in equipment requirement and excellent in product performance, and the price of a novel heating body is expected to be greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano-conductive ceramic preparation, and in particular relates to a method for preparing CuAlO2-phase alumina-based conductive ceramic. Background Art

[0002] Electric heating materials and related devices provide convenience and simplicity for people's lives and have permeated every aspect of modern society. Research and development in these materials continues unabated. Based on their primary method of heat generation and heat transfer, electric heating materials can be categorized as high-temperature and low-temperature heating elements. High-temperature heating elements primarily utilize radiation, supplemented by convection and conduction, and are used in applications such as industrial furnaces. Key materials include silicon carbide, molybdenum disilicide, and heating wire. Civilian applications, however, are increasingly favoring low-temperature heating materials and devices due to safety concerns, such as the prohibition of open flames and the prevention of fires in daily life. These materials primarily utilize conduction and convection as the primary means of heat transfer. These include both membrane and bulk heating elements. Mainstream materials include BaTiO3-based PTCR ceramic heating elements and composite heating elements composed of conductive metals or carbonaceous materials mixed with polymers.

[0003] PTCR ceramic heaters offer advantages over resistance wire heaters, such as lower energy consumption and more stable heat generation. They are technologically mature, feature a simple structure, flexible layout, and easy installation. However, the low thermal conductivity of barium titanate-based materials necessitates strong convection heat transfer to dissipate heat. This results in a complex heat sink structure and the need for a strong ventilation system, which inevitably generates noise during operation. While this brings convenience to daily life, it also introduces annoyance.

[0004] In recent years, a new type of alumina ceramic heater, the so-called Metal Ceramic Heater (MCH), has been developed. This high-tech, energy-efficient heating element utilizes a high-thermal conductivity alumina ceramic as a base, with heat-resistant refractory metals forming the heating circuit. Co-fired at 1600°C through a series of specialized processes, the heating elements are co-fired. This heating element is widely used in heating devices across all aspects of daily life. Instead of using aluminum oxide to generate heat, this heating element utilizes the metal W or Mo within the aluminum oxide. This element offers advantages such as corrosion resistance, high temperature resistance, long life, high energy efficiency, uniform temperature, excellent thermal conductivity, and rapid thermal compensation. MCH ceramic heaters are a new type of highly efficient, environmentally friendly, and energy-saving ceramic heating element. Compared to PTC ceramic heaters, they offer 20-30% less energy than PTC ceramic heaters, achieving the same heating effect. However, this type of heater requires high-temperature co-firing of the metal and aluminum oxide, resulting in a complex and energy-intensive manufacturing process, significantly increasing costs.

[0005] Al2O3 ceramics are one of the mainstream materials for thermally conductive substrates due to their excellent high-temperature resistance, high mechanical strength, high insulation, and high thermal conductivity. However, we have discovered that during the preparation of black alumina ceramics, certain dopants can easily cause the insulation of alumina to be lost. Based on this, we have further improved its conductivity through process adjustments, thus forming alumina conductive ceramics. Research has shown that the conductivity of this alumina originates from the semiconductor conductive phase at the grain boundaries of the alumina ceramics, which provides a new direction for the further development and research of alumina ceramic heating elements. As a heating element, this material not only has the high thermal conductivity and high strength of alumina, but can also generate heat directly when powered, achieving two goals at once, thus forming a truly new type of alumina ceramic heating element. The present invention can significantly reduce the sintering temperature of alumina from the original 1600°C to below 1300°C. Without complex processes and the need for expensive raw materials, this new type of alumina conductive heating ceramic has low energy consumption, simple processes, low equipment requirements, excellent product performance, and the price of the new heating element is expected to be significantly reduced. Summary of the Invention

[0006] In response to the shortcomings of the existing technology, the present invention provides a method for preparing alumina-based conductive ceramics with CuAlO2 as the conductive phase. By adding the semiconductor component CuAlO2 phase to the alumina ceramic and making it continuously distributed along the alumina grain boundaries to form a conductive path, the alumina ceramic is transformed from an insulator into a conductive heating element. Specifically, the conductive agent, sintering aid and alumina powder are mixed in a certain proportion, ball-milled and formed, and then pressed and sintered to form an alumina electric heating element.

[0007] A method for preparing CuAlO2-phase alumina-based conductive ceramics, comprising the following steps:

[0008] (1) Weighing a conductive agent, a sintering aid, and alumina, mixing them in proportion and uniformly mixing them to obtain a mixture;

[0009] (2) forming the mixture into a ceramic green body by a certain method;

[0010] (3) The ceramic green body is sintered in air and then kept warm to obtain an alumina-based conductive ceramic.

[0011] in:

[0012] In the step (1), the conductive agent is a transition element oxide selected from one or more of CuO, Fe2O3, ZnO, MnO2, and NiO. The amount of the conductive agent used is 10% to 70% of the alumina in terms of mass fraction. When multiple conductive agents are selected, the ratios between the multiple substances are: CuO 10% to 60%, Fe2O3 0% to 5%, ZnO 0% to 20%, MnO2 0% to 10%, and NiO 0% to 15%.

[0013] In the step (1), the sintering aid is selected from one or more of SiO2 and clay. The amount of the sintering aid is 0-20% of the alumina in terms of mass fraction. When multiple sintering aids are selected, the amount of SiO2 added is 0-10%, and the amount of clay added is 0-10%.

[0014] In the step (1), the mixing method is ball milling, grinding or vibration milling.

[0015] In the step (2), the forming method is dry pressing, casting, film rolling or isostatic pressing.

[0016] In the step (3), the sintering temperature is 1000-1500° C., and the holding time is 10-300 minutes.

[0017] In the step (3), the resistivity of the alumina-based conductive ceramic obtained is 0.1 to 0.8 MΩ·cm.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. This method can not only realize low-temperature sintering of alumina ceramics, but also generally reduce the sintering temperature of alumina ceramics from 1600°C to 1000-1500°C.

[0020] 2. Alumina is usually a typical insulator. This method can transform the sintered alumina ceramic from an insulator to a conductor.

[0021] 3. This method avoids the complex atmosphere sintering and can achieve ceramic semiconducting by sintering only in air.

[0022] 4. This method is simple to operate, does not require complex processes and equipment, and has low raw material costs and energy consumption required for preparation. A simple normal pressure molding method can be used to prepare ceramic sheets that are easy to sinter. The resulting conductive heating ceramic products have excellent performance and the price is expected to be significantly reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD patterns of the alumina-based conductive ceramics prepared in Examples 1, 2, 3, and 4 of the present invention;

[0024] Figure 2 SEM image of the alumina-based conductive ceramic prepared in Example 1 of the present invention;

[0025] Figure 3 SEM image of the alumina-based conductive ceramic prepared in Example 4 of the present invention;

[0026] Figure 4 XRD pattern of the alumina-based conductive ceramic prepared in Example 5 of the present invention;

[0027] Figure 5 XRD pattern of the alumina-based conductive ceramic prepared in Example 6 of the present invention;

[0028] Figure 6 SEM image of the alumina-based conductive ceramic prepared in Example 6 of the present invention;

[0029] Figure 7 XRD pattern of the alumina-based conductive ceramic prepared in Example 7 of the present invention;

[0030] Figure 8 SEM image of the alumina-based conductive ceramic prepared in Example 7 of the present invention;

[0031] Figure 9 XRD pattern of the alumina-based conductive ceramic prepared in Example 8 of the present invention;

[0032] Figure 10 SEM image of the alumina-based conductive ceramic prepared in Example 8 of the present invention. DETAILED DESCRIPTION

[0033] The invention will be further described below in conjunction with the embodiments:

[0034] The conductive agent used in the present invention is a substance that forms a conductive phase during the sintering process of alumina, such as CuAlO2; the sintering aid is a raw material that can reduce the sintering temperature of alumina, such as SiO2 and clay.

[0035] Example 1

[0036] A method for preparing CuAlO2-phase alumina-based conductive ceramics, comprising the following steps:

[0037] (1) Weigh 0.5 g of ultrafine silica powder, 3 g of copper oxide powder, and 6.5 g of aluminum oxide powder and grind them in a mortar for about 30 min to mix them evenly to obtain a mixture;

[0038] (2) dry pressing the mixture under 1 MPa to obtain a ceramic green body;

[0039] (3) The ceramic green body was sintered at 1300°C in air and then kept warm for 120 minutes to obtain an alumina-based conductive ceramic.

[0040] The resistivity of the alumina-based conductive ceramic prepared in this embodiment is 0.4 MΩ·cm, and its XRD pattern is shown in FIG. Figure 1 As shown in Figure 2, the main phases of the ceramics sintered at this temperature are alumina, cuprous aluminate, a small amount of copper oxide and silicon dioxide phases; the SEM image of alumina-based conductive ceramics is shown in Figure 2. Figure 2 As shown in the figure, it can be seen that the ceramic has few pores, uniform particles and good density.

[0041] Example 2

[0042] A method for preparing CuAlO2-phase alumina-based conductive ceramics, comprising the following steps:

[0043] (1) Weigh 0.5 g of ultrafine silica powder, 3.5 g of copper oxide powder, and 6 g of aluminum oxide powder and grind them in a mortar for about 30 min to mix them evenly to obtain a mixture;

[0044] (2) dry pressing the mixture under 1 MPa to obtain a ceramic green body;

[0045] (3) The ceramic green body was sintered at 1300°C in air and then kept warm for 120 minutes to obtain an alumina-based conductive ceramic.

[0046] The resistivity of the alumina-based conductive ceramic prepared in this embodiment is 0.4 MΩ·cm, and its XRD pattern is shown in FIG. Figure 1 As shown in Figure 2, the main phases of the ceramics sintered at this temperature are alumina, cuprous aluminate, a small amount of copper oxide and silicon dioxide phases; the SEM image of alumina-based conductive ceramics is similar to that of Figure 2 The obtained ceramics have fewer pores, uniform particles and good density.

[0047] Example 3

[0048] A method for preparing CuAlO2-phase alumina-based conductive ceramics, comprising the following steps:

[0049] (1) Weigh 0.5 g of ultrafine silicon dioxide powder, 3.7 g of copper oxide powder, and 5.8 g of aluminum oxide powder and grind them in a mortar for about 30 min to mix them evenly to obtain a mixture;

[0050] (2) dry pressing the mixture under 1 MPa to obtain a ceramic green body;

[0051] (3) The ceramic green body was sintered at 1300°C in air and then kept warm for 120 minutes to obtain an alumina-based conductive ceramic.

[0052] The resistivity of the alumina-based conductive ceramic prepared in this embodiment is 0.3 MΩ·cm, and its XRD pattern is shown in FIG. Figure 1 As shown in Figure 2, the main phases of the ceramics sintered at this temperature are alumina, cuprous aluminate, a small amount of copper oxide and silicon dioxide phases; the SEM image of alumina-based conductive ceramics is similar to that of Figure 2 The obtained ceramics have fewer pores, uniform particles and good density.

[0053] Example 4

[0054] A method for preparing CuAlO2-phase alumina-based conductive ceramics, comprising the following steps:

[0055] (1) Weigh 0.5 g of clay, 3.5 g of copper oxide powder, and 6 g of aluminum oxide powder and grind them in a mortar for about 30 min to mix them evenly to obtain a mixture;

[0056] (2) dry pressing the mixture under 1 MPa to obtain a ceramic green body;

[0057] (3) The ceramic green body was sintered at 1300°C in air and then kept warm for 120 minutes to obtain an alumina-based conductive ceramic.

[0058] The resistivity of the alumina-based conductive ceramic prepared in this embodiment is 0.2 MΩ·cm, and its XRD pattern is shown in FIG. Figure 1 As shown in Figure 2, the main phases of the ceramics sintered at this temperature are alumina, cuprous aluminate, a small amount of copper oxide and silicon dioxide phases; the SEM image of alumina-based conductive ceramics is shown in Figure 2. Figure 3 As shown in the figure, it can be seen that the ceramic has few pores, uniform particles and good density.

[0059] Example 5

[0060] A method for preparing CuAlO2-phase alumina-based conductive ceramics, comprising the following steps:

[0061] (1) Weigh 0.5 g of ultrafine silica powder, 3.5 g of copper oxide powder, and 6 g of aluminum oxide powder and grind them in a mortar for about 30 min to mix them evenly to obtain a mixture;

[0062] (2) dry pressing the mixture under 1 MPa to obtain a ceramic green body;

[0063] (3) The ceramic green body was sintered at 1500°C in air and then kept warm for 120 minutes to obtain an alumina-based conductive ceramic.

[0064] The resistivity of the alumina-based conductive ceramic prepared in this embodiment is 0.3 MΩ·cm, and its XRD pattern is shown in FIG. Figure 4 As shown in Figure 2, the main phases of the ceramics sintered at this temperature are alumina, cuprous aluminate, a small amount of copper oxide and silicon dioxide phases; the SEM image of alumina-based conductive ceramics is similar to that of Figure 2 The obtained ceramics have fewer pores, uniform particles and good density.

[0065] Example 6

[0066] A method for preparing CuAlO2-phase alumina-based conductive ceramics, comprising the following steps:

[0067] (1) Weigh 0.5 g of ultrafine silica powder, 0.5 g of clay, 3 g of copper oxide powder, and 6 g of aluminum oxide powder and grind them in a mortar for about 30 min to mix them evenly to obtain a mixture;

[0068] (2) dry pressing the mixture under 1 MPa to obtain a ceramic green body;

[0069] (3) The ceramic green body was sintered at 1300°C in air and then kept warm for 120 minutes to obtain an alumina-based conductive ceramic.

[0070] The resistivity of the alumina-based conductive ceramic prepared in this embodiment is 0.4 MΩ·cm, and its XRD pattern is shown in FIG. Figure 5 As shown in Figure 2, the main phases of the ceramics sintered at this temperature are alumina, copper aluminate, a small amount of copper oxide and silicon dioxide phases; the SEM image of alumina-based conductive ceramics is shown in Figure 2. Figure 6 As shown in the figure, it can be seen that the ceramic has few pores, uniform particles, and good density. It can also be seen that cuprous aluminate with a layered structure is mainly distributed near the grain boundaries, making the alumina particles interconnected, thereby realizing the semiconductivity of the alumina ceramic.

[0071] Example 7

[0072] A method for preparing CuAlO2-phase alumina-based conductive ceramics, comprising the following steps:

[0073] (1) Weigh 0.3 g of ultrafine silica powder, 0.2 g of clay, 3.5 g of copper oxide powder, and 6 g of aluminum oxide powder and grind them in a mortar for about 30 min to mix them evenly to obtain a mixture;

[0074] (2) dry pressing the mixture under 1 MPa to obtain a ceramic green body;

[0075] (3) The ceramic green body was sintered at 1300°C in air and then kept warm for 120 minutes to obtain an alumina-based conductive ceramic.

[0076] The resistivity of the alumina-based conductive ceramic prepared in this embodiment is 0.7 MΩ·cm, and its XRD pattern is shown in FIG. Figure 7 As shown in Figure 2, the main phases of the ceramics sintered at this temperature are alumina, copper aluminate, a small amount of copper oxide and silicon dioxide phases; the SEM image of alumina-based conductive ceramics is shown in Figure 2. Figure 8 As shown in the figure, it can be seen that the ceramic has few pores, uniform particles and good density.

[0077] Example 8

[0078] A method for preparing CuAlO2-phase alumina-based conductive ceramics, comprising the following steps:

[0079] (1) Weigh 0.5 g of ultrafine silica powder, 0.5 g of clay, 3.5 g of copper oxide powder, and 5.5 g of aluminum oxide powder and grind them in a mortar for about 30 min to mix them evenly to obtain a mixture;

[0080] (2) dry pressing the mixture under 1 MPa to obtain a ceramic green body;

[0081] (3) The ceramic green body was sintered at 1300°C in air and then kept warm for 120 minutes to obtain an alumina-based conductive ceramic.

[0082] The resistivity of the alumina-based conductive ceramic prepared in this embodiment is 0.4 MΩ·cm, and its XRD pattern is shown in FIG. Figure 9 As shown in Figure 2, the main phases of the ceramics sintered at this temperature are alumina, copper aluminate, a small amount of copper oxide and silicon dioxide phases; the SEM image of alumina-based conductive ceramics is shown in Figure 2. Figure 10 As shown in the figure, it can be seen that the ceramic has few pores, uniform particles and good density.

Claims

1. A method for preparing CuAlO2-phase alumina-based conductive ceramics, characterized in that: The specific steps include: (1) weighing a conductive agent, a sintering aid, and alumina, mixing them according to a proportion, and mixing them evenly to obtain a mixture; (2) forming the mixed material by a certain method to obtain a ceramic green body; (3) The ceramic green body is sintered in air and then kept warm to obtain an alumina-based conductive ceramic.

2. The method for preparing CuAlO2-phase alumina-based conductive ceramic according to claim 1, characterized in that: In the step (1), the conductive agent is a transition element oxide, selected from one or more of CuO, Fe2O3, ZnO, MnO2, and NiO. The amount of the conductive agent used is 10% to 70% of the alumina in terms of mass fraction. When multiple conductive agents are selected, the ratios between the multiple substances are: CuO 10 to 60%, Fe2O3 0 to 5%, ZnO 0 to 20%, MnO2 0 to 10%, and NiO 0 to 15%.

3. The method for preparing a CuAlO2-phase alumina-based conductive ceramic according to claim 1, characterized in that: In the step (1), the sintering aid is selected from one or more of SiO2 and clay. The amount of the sintering aid is 0-20% of the alumina in terms of mass fraction. When multiple sintering aids are selected, the amount of SiO2 added is 0-10%, and the amount of clay added is 0-10%.

4. The method for preparing a CuAlO2-phase aluminum oxide-based conductive ceramic according to claim 1, characterized in that: In the step (1), the mixing method is ball milling, grinding or vibration milling.

5. The method for preparing CuAlO2-phase aluminum oxide-based conductive ceramic according to claim 1, characterized in that: In the step (2), the forming method is dry pressing, casting, film rolling or isostatic pressing.

6. The method for preparing CuAlO2-phase aluminum oxide-based conductive ceramic according to claim 1, characterized in that: In the step (3), the sintering temperature is 1000-1500° C., and the holding time is 10-300 min.

7. The method for preparing CuAlO2-phase aluminum oxide-based conductive ceramic according to claim 1, characterized in that: In the step (3), the resistivity of the alumina-based conductive ceramic obtained is 0.1 to 0.8 MΩ·cm.

Citation Information

Patent Citations

  • Aluminum oxide anti-static ceramic material and preparation method thereof

    CN105236941A

  • Electroconductive ceramic sintered material

    JP1990153859A

  • Electrically conductive alumina-based composite ceramic and its production

    JP1996119721A

Cited By

  • Simple method for preparing conductive aluminum oxide ceramic

    CN120483765A